2013
DOI: 10.1039/c3cp52070f
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic characterization of potassium fluoroborohydrides

Abstract: Metal borohydrides are intensively investigated in the context of energy storage due to their high hydrogen content. 1 Recently, 15 there has also been reported high Li-ion conductivity in several Li-containing borohydrides, such as ortho-LiBH 4 2 and LiCe(BH 4 ) 3 Cl, 3 which makes them interesting as solid electrolytes in Li-ion batteries. Partial substitution of the tetraborohydride anions (BH 4 -) with heavy halides (Cl -, Br -or I -) 20 has been successfully used to alter the properties of borohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…The hydrogen release from KBH 2.8 F 1.2 takes place 433°C lower than it does in pure KBH 4 [63]. However, some of the obtained materials, specifically NaB(H 1-x F x ) 4 , appear to have relatively low thermal stability, and the released hydrogen may be contaminated with significant amounts of boron fluorides and/or borane gases and may lead to the formation of significant amounts of M 2 B 12 H 12 [64][65][66][67].…”
Section: Anion Substitution In Metal Borohydridesmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen release from KBH 2.8 F 1.2 takes place 433°C lower than it does in pure KBH 4 [63]. However, some of the obtained materials, specifically NaB(H 1-x F x ) 4 , appear to have relatively low thermal stability, and the released hydrogen may be contaminated with significant amounts of boron fluorides and/or borane gases and may lead to the formation of significant amounts of M 2 B 12 H 12 [64][65][66][67].…”
Section: Anion Substitution In Metal Borohydridesmentioning
confidence: 99%
“…However, thermodynamic stabilization is also possible, as seen for NaMgH 2 F [61]. The first complex hydride with fluorine substitution was prepared by hydrogenation of the system NaF-Al, which provided complex hydride Na 3 AlH 6-x F x [62,63] [65]. Both of these phases, which are isostructural with KBH 4 , are stable at room temperature.…”
Section: Anion Substitution In Metal Borohydridesmentioning
confidence: 99%
“…25 Experimental reports indicate fluorine substitution in studies of MgB 2 -LiF and LiBH 4 -TiF 3 and also for the KBH 4 -KBF 4 system. [29][30][31] In this paper, the physical, structural and hydrogen storage properties of the NaBH 4 -NaBF 4 composite are investigated using in situ synchrotron radiation powder X-ray diffraction (SR-PXD), solid-state magic-angle spinning (MAS) NMR spectroscopy, infrared spectroscopy (IR), simultaneous differential scanning calori-metry (DSC), thermogravimetric analysis (TGA), and Sieverts method. DFT calculations on isolated BF 4 x H x ions were also performed and spectral parameters were computed.…”
Section: Introductionmentioning
confidence: 99%
“…prompted us to evaluate the prospect of applying this approach to a more general synthesis of mono‐substituted borohydride anions, such as [H 3 BX] − (X=halogen or pseudo‐halogen). However, a literature search revealed that the reaction of equimolar amounts of KF and BH 3 ⋅ SMe 2 in refluxing dimethoxyethane had already previously been studied and resulted in a complete redistribution of ligands, yielding discrete phases of KBH 4 and KBF 4 . Therefore, no further experiments were carried out in this direction.…”
Section: Resultsmentioning
confidence: 99%